2016
DOI: 10.1097/aap.0000000000000380
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Dose Dependently Enhances the Local Anesthetic Action of Lidocaine in Inferior Alveolar Nerve Block

Abstract: Dexmedetomidine dose dependently enhances the local anesthetic action of lidocaine in humans. Dexmedetomidine at 2.5 ppm produces similar enhancement of local anesthesia effect as addition of 1:80,000 AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 28 publications
(40 reference statements)
0
13
0
Order By: Relevance
“…When DEX is combined with a local anesthetic agent for TAP block, it can prolong the duration of block [31] or improve postoperative pain and recovery from anesthesia [32], which is possibly due to local vasoconstriction in peripheral nerves [33] or direct inhibition in peripheral nerve action [34]. DEX was found to dose-dependent enhance of the local anesthetic effect of lidocaine in rats [35] and in healthy volunteers [36].…”
Section: Discussionmentioning
confidence: 99%
“…When DEX is combined with a local anesthetic agent for TAP block, it can prolong the duration of block [31] or improve postoperative pain and recovery from anesthesia [32], which is possibly due to local vasoconstriction in peripheral nerves [33] or direct inhibition in peripheral nerve action [34]. DEX was found to dose-dependent enhance of the local anesthetic effect of lidocaine in rats [35] and in healthy volunteers [36].…”
Section: Discussionmentioning
confidence: 99%
“…This result can be explained by the fact that dexmedetomidine has no antitussive effects, and the passage of a flexible bronchoscope through the vocal cords can lead to coughing (5). Recently, the use of dexmedetomidine as an additive to local anaesthetics was reported to have several advantages over conventional intravenous administration (6,7). Animal experiments have indicated that the local application of dexmedetomidine to the airway can expand the smooth muscle of the trachea and may inhibit the cough response (8).…”
Section: Introductionmentioning
confidence: 99%
“…DEX was found to dose-dependent enhance of the local anesthetic effect of lidocaine in rats [28] and in healthy volunteers [29].…”
Section: Discussionmentioning
confidence: 92%